2022
DOI: 10.1177/0095327x221076555
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Sociological Profile of Women Who Have Completed Elite Military Combat Training

Abstract: More than 75 women have successfully graduated from the U.S. Army Ranger Course since the integration of women into elite military combat training. This study sought to identify the psychological characteristics and sociological variables that contributed to their motivation and success. A guided interview and demographic and psychological questionnaires were used to assess characteristics of 13 women who successfully completed elite military combat training. Collectively, these women were college graduates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…It has been previously suggested that these first female elite warfighters (FEW) will be protected against the commonly observed musculoskeletal injuries, such as bone stress reactions (8) by greater lean and bone mass compared with other female Soldiers and some athletes. Without question, this group has a distinctly defined mental outlook, including a very high degree of self-motivation and grit, as already reported (9). However, the physiological features of the FEW have not been well defined in a systematic way.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…It has been previously suggested that these first female elite warfighters (FEW) will be protected against the commonly observed musculoskeletal injuries, such as bone stress reactions (8) by greater lean and bone mass compared with other female Soldiers and some athletes. Without question, this group has a distinctly defined mental outlook, including a very high degree of self-motivation and grit, as already reported (9). However, the physiological features of the FEW have not been well defined in a systematic way.…”
supporting
confidence: 68%
“…Background information on demographics including family up-bringing, education and military service were collected using guided interviews and a study-specific questionnaire. Much of this psychosocial data have been reported elsewhere (9).…”
Section: Demographic Data Collectionmentioning
confidence: 89%
“…The earlier cohorts of Marine women did not serve in combat roles, nor did they train for such roles, and they were even fewer in number. Additional assessments of the psychological and psychosocial profiles of this changing group could also provide unique insights into ideal selection, stressors and readiness of military women 23 24…”
Section: Discussionmentioning
confidence: 99%
“…To study the PSWB profile of the participants, instruments proposed by Tharion et al [ 16 ] were used, i.e., (i) Grit-S (Short Grit Scale) and (ii) DRS-II M (Dispositional Resilience Scale II Military Version).…”
Section: Methodsmentioning
confidence: 99%